Pengaruh Stres Kerja terhadap Turnover Intetion dimediasi Job Embeddedness dan Komitmen Organiasional pada CV Filo Company, Klaten - Pamungkas, Kristuhadi Catur; Winarno, Winarno; Warsiki, AYN (Jurnal Manajemen, 2023)
This research was conducted on CV Filo Company with the aim of knowing the direct effect of work stress on turnover intention, the indirect effect of job stress on turnover intetion with job job embeddedness as a mediating variabel, and the inderect effect of job stress on turnover intention with organizational commitment as a mediation variabel. Quantitative research method used in this study using Smart PLS 3.0 program as an analytical tool. Samplong using non-probability sampling that is saturated sample or census, the sample is this study were all employees of CV Filo Company with 32 employees. Consisting of 26 women and 6 men, the majority are 21-24 years old, the majority have diploma/bachelor degress, and the majority have worked for 1-12 months. The data collection techniwue used a questionnaire distributed online, the research instrument used a Likert scale. Methods of data analysis through validity, reliability, and hypothesis testing. In this study, it was shown that work stress had no direct effect on turnover intention, indicated by a coefficient value of 0.119 and p-value of 0.354 (>0.05), hypothesis 1 was rejected. Job stress has a positive effect on turnover intention with job emebeddedness as a mediaton indicated by a coefficient value of 0.433 and p-value of 0.006 (<0.05), hypothesis 2 supported. Job stress has a positive effect on turnover intention with organizational commitment as a mediaton indicated by a coefficient value of 0.316 and p-value of 0.014 (<0.05), hypothesis 3 supported.